2017
DOI: 10.1080/15384101.2017.1380133
|View full text |Cite
|
Sign up to set email alerts
|

Dynein promotes porcine oocyte meiotic progression by maintaining cytoskeletal structures and cortical granule arrangement

Abstract: Cytoplasmic dynein is a family of cytoskeletal motor proteins that move towards the minus-end of the microtubules to perform functions in a variety of mitotic processes such as cargo transport, organelle positioning, chromosome movement and centrosome assembly. However, its specific roles during mammalian oocyte meiosis have not been fully defined. Herein, we investigated the critical events during porcine oocyte meiotic maturation after inhibition of dynein by Ciliobrevin D treatment. We found that oocyte mei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Ac α-Tubulin K40 is one of the most important post-translational modifications of microtubules (Schatten, Simerly et al 1988, Ly, Elkhatib et al 2016. Studies have shown that acetylation affects the stability of microtubules, and an increase in acetylated α-tubulin levels can enhance the stability of mitotic microtubules (Miao, Zhou et al 2017, Steinhauser, Kloble et al 2017. We hypothesized that the sperm-borne small RNA may regulate cytoskeleton function through the Ac α-tubulin K40, thus affecting microtubule assembly, cytokinesis, and chromosome segregation, and further affecting the embryonic first cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Ac α-Tubulin K40 is one of the most important post-translational modifications of microtubules (Schatten, Simerly et al 1988, Ly, Elkhatib et al 2016. Studies have shown that acetylation affects the stability of microtubules, and an increase in acetylated α-tubulin levels can enhance the stability of mitotic microtubules (Miao, Zhou et al 2017, Steinhauser, Kloble et al 2017. We hypothesized that the sperm-borne small RNA may regulate cytoskeleton function through the Ac α-tubulin K40, thus affecting microtubule assembly, cytokinesis, and chromosome segregation, and further affecting the embryonic first cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is a further proof of the key importance of microfilaments in oocytes maturation and CGs dynamics. Miao et al described the important role of dynein (cytoskeletal motor proteins) in the meiotic progression of porcine oocytes through the regulation of cytoskeletal dynamics, including the stability of microtubules [46], reflecting the distribution of CGs and ovastacin exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used porcine oocytes as a model to explore the function of SIRT6 on meiotic maturation, as the developmental and physiological indexes of porcine oocytes including the diameter of oocytes and maturation time are more similar to humans in comparison with mice ( Schatten and Sun, 2009 ; Miao et al, 2017 ). We found that inhibition of SIRT6 activity impaired both nuclear and cytoplasmic maturation of oocytes, including the abnormal cytoskeleton assembly and cortical granule (CG) dynamics.…”
Section: Introductionmentioning
confidence: 99%